2021
DOI: 10.3389/fenrg.2021.705944
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Cooled Fast Reactor Annular UN Fuel Design and Development of Performance Analysis Program

Abstract: A kind of annular uranium nitride (UN) fuel suitable for lead-cooled fast reactor applications has been designed in this study. The design is directly targeting two main issues of UN fuel: severe swelling and thermal decomposition of UN fuel at high temperatures. A performance analysis program based on FORTRAN programming language has been developed for UN fuel in fast reactors. The program contains heat transfer, fuel stress-strain analysis, cladding stress-strain analysis, fission gas release and fuel-claddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In response to this problem, they proposed an annular fuel design structure. The results show that the use of annular fuel design structure can effectively reduce the core temperature of the fuel, thereby solving not only the problem of fuel swelling, but also the problem of thermal decomposition [18]. Mum et al found that when U-10Zr fuel is loaded in a small lead-cooled reactor, if there is an air gap between the fuel and the cladding, the fuel centerline temperature can be as high as 2351 K, at which point the fuel will melt.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this problem, they proposed an annular fuel design structure. The results show that the use of annular fuel design structure can effectively reduce the core temperature of the fuel, thereby solving not only the problem of fuel swelling, but also the problem of thermal decomposition [18]. Mum et al found that when U-10Zr fuel is loaded in a small lead-cooled reactor, if there is an air gap between the fuel and the cladding, the fuel centerline temperature can be as high as 2351 K, at which point the fuel will melt.…”
Section: Introductionmentioning
confidence: 99%
“…The metallurgy and mechanical behavior of Uranium Nitride (UN) is very different from that of uranium oxides [ 13 , 14 ]. Although UN fuel has a high melting point (3120 K) it starts undergoing decomposition at about 2000K [ 15 ] due to low partial pressure of nitrogen. Thus, fuel temperature should be kept within this limit during operation.…”
Section: Introductionmentioning
confidence: 99%
“…An elaborate performance analysis for uranium nitride fuel for a lead cooled fast reactor has been carried out by Yuan et al [ 15 ] for thermal loading of 30 kW/m and 45 kW/m power densities as well as for a transient with 60 kW/m. Another similar work by Liu et al [ 17 ], carries out a thermal-hydraulic design analysis of a 500kW th 45 % enriched UN fueled MNR using potassium in a heat pipe.…”
Section: Introductionmentioning
confidence: 99%